2022
DOI: 10.3390/ijerph19052696
|View full text |Cite
|
Sign up to set email alerts
|

Association between Noise Annoyance and Mental Health Outcomes: A Systematic Review and Meta-Analysis

Abstract: To date, most studies of noise and mental health have focused on noise exposure rather than noise annoyance. The purpose of this systematic review and meta-analysis was to evaluate whether the available evidence supports an adverse association between noise annoyance and mental health problems in people. We carried out a literature search of Web of Science, PubMed, Scopus, PsycINFO, and conference proceedings published between 2000 and 2022. Thirteen papers met the inclusion criteria. We conducted meta-analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Taking this fact into account, self-reported noise measures could be a better indicator for annoyance among noise-sensitive people than purely modelled levels (Gong et al, 2022). In the current study, there was no evaluation of the participant's noise sensitivity, but the interpretation of answers to two different questions can give some information about noise sensitivity.…”
Section: Discussionmentioning
confidence: 80%
“…Taking this fact into account, self-reported noise measures could be a better indicator for annoyance among noise-sensitive people than purely modelled levels (Gong et al, 2022). In the current study, there was no evaluation of the participant's noise sensitivity, but the interpretation of answers to two different questions can give some information about noise sensitivity.…”
Section: Discussionmentioning
confidence: 80%
“…Regarding environmental stressors, their effects on the components of SWB have been extensively studied in psychology. Through a non-exhaustive review of this literature, we have shown that the 4 main categories of environmental stressors, namely daily hassles, ambient stressors (especially noise annoyance), stressful life events, and cataclysmic events (especially floods), are associated with short and in some cases long term degradation of SWB, especially through the decrease in life satisfaction [28,32,44,46].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in their meta-analysis and systematic review, Gong et al (2022) found that noise-annoyed people had a, respectively, 55% (6 studies) and 23% (8 studies) increased risk of anxiety and depressive symptoms compared to people with low noise annoyance [32]. This detrimental effect of noise annoyance on affective state (and thus on SWB) would also be devoid of a habituation effect [33] and would also concern children [34].…”
Section: Ambient Stressorsmentioning
confidence: 99%
“…Community noise has been linked to numerous negative health effects, including high annoyance (1,2), poor mental health (3), obesity (4), hypertension (5), heart disease (6)(7)(8), increased risk of diabetes (9), and sleep disturbance (10,11). Environmental noise affects some population groups more than others (12).…”
Section: Introductionmentioning
confidence: 99%